2010
DOI: 10.1002/art.27442
|View full text |Cite
|
Sign up to set email alerts
|

Markers of oxidative and nitrosative stress in systemic lupus erythematosus: Correlation with disease activity

Abstract: Objective. Free radical-mediated reactions have been implicated as contributors in a number of autoimmune diseases, including systemic lupus erythematosus (SLE). However, the potential for oxidative/ nitrosative stress to elicit an autoimmune response or to contribute to disease pathogenesis, and thus be useful when determining a prognosis, remains largely unexplored in humans. This study was undertaken to investigate the status and contribution of oxidative/ nitrosative stress in patients with SLE.Methods. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
176
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(188 citation statements)
references
References 52 publications
8
176
0
1
Order By: Relevance
“…Increased level of MDA in the serum 18 and in the erythrocytes 19 was reported in SLE patients. Wang et al 20 and Shah et al 21 associated stronger oxidative stress response with higher SLEDAI scores, similar to the previous report of Tewthanom et al 18 However, we have not identifi ed, in our study, the association of MDA or SH levels with SLEDAI scores. The high levels of MDA in SLE patients indicate that the lipid cell membrane was attacked and that MDA can be a good marker of oxidative stress in this disease.…”
supporting
confidence: 90%
“…Increased level of MDA in the serum 18 and in the erythrocytes 19 was reported in SLE patients. Wang et al 20 and Shah et al 21 associated stronger oxidative stress response with higher SLEDAI scores, similar to the previous report of Tewthanom et al 18 However, we have not identifi ed, in our study, the association of MDA or SH levels with SLEDAI scores. The high levels of MDA in SLE patients indicate that the lipid cell membrane was attacked and that MDA can be a good marker of oxidative stress in this disease.…”
supporting
confidence: 90%
“…TCE is known to generate free radicals, and cause increased lipid peroxidation in both in vivo and in vitro models (Khan et al, 2001;Wang et al, 2007). Several lines of evidence in lupus-prone mice showed that increased generation of ROS was correlated with increased autoantibodies production, illustrating a potential role of oxidative stress in TCE induced autoimmune response (Wang et al, 2007(Wang et al, , 2010. Although there is a large body of literature addressing immune responses during environmental chemicals exposure, the TCE immunotoxicity is poorly understood.…”
Section: Tce Induces Vascular and Degenerative Changes In Hepatic Arcmentioning
confidence: 99%
“…Increasing evidence suggests that ROS-modified proteins such as protein carbonyls and lipid peroxidation-derived aldehydes [LPDAs, including malondialdehyde (MDA) and 4-hydroxynonenal (HNE)]-protein adducts may elicit an autoimmune response and contribute to disease pathogenesis (Ben Mansour et al, 2010). Indeed, higher levels of MDA-/HNE-modified proteins and protein carbonyls have been seen in autoimmune disease patients (Ben Mansour et al, 2010;Wang et al, 2010), illustrating a role for these oxidative modified proteins in autoimmune diseases. Oxidative stress can affect cell integrity only when antioxidant mechanisms are no longer able to cope with free radical generation.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) have been considered as risk and enhancer factors for autoimmune diseases [4], and free radical-mediated reactions are implicated in SLE. Oxidative stress has a potential to elicit an autoimmune response and to contribute to the disease pathogenesis thus being useful when determining its prognosis [5]. Alopecia and lupus nephritis are remarkably associated with oxidative stress and impaired antioxidant systems in SLE patients [4].…”
Section: Introductionmentioning
confidence: 99%